A decade of geriatric traumatic brain injuries in Finland: population-based trends. (5th March 2020) - Posti, Jussi P; Sipilä, Jussi O T; Luoto, Teemu M; Rautava, Päivi; Kytö, Ville
Abstract: Background: we investigated trends of traumatic brain injury (TBI)-related hospitalisations, deaths, acute neurosurgical operations (ANO), and lengths of hospital stay (LOS) in patients aged ≥70 years in Finland using a population-based cohort. Methods: nationwide databases were searched for all admissions with a TBI diagnosis as well as later deaths for persons ≥70 years of age during 2004–2014. Results: the study period included 20, 259 TBI-related hospitalisations (mean age = 80.7 years, men = 48.9%). The incidence of TBI-related hospitalisations was 283/100, 000 person-years with an estimated overall annual increase of 2.9% (95% CI: 0.4–5.9%). There was an annual decrease of 2.2% in in-hospital mortality (IHM) in men (95% CI: 0.1–4.3%), with no change in women or overall. There was an annual decrease of 1.1% in odds for ANOs among hospitalised overall (95% CI: 0.1–2.1%) and of 1.4% in men (95% CI: 0.0–2.7%), while no change was observed in women. LOS decreased annually by 2.5% (95% CI: 2.1–2.9%). The incidence of TBI-related deaths was 70/100, 000 person-years with an estimated annual increase of 1.6% in women (95% CI: 0.2–2.9%), but no change in men or overall. Mean ages of TBI-related admissions and deaths increased ( P < 0.001). Interpretation: the incidence rate of geriatric TBI-related hospitalisations increased, especially in women, but LOS and the rate of ANOs among hospitalised decreased. The overall TBI-related mortality remained stable, and IHM decreased in men, while in women, the overall mortality increased and IHM remained stable. However, the overall incidence rates of TBI-related hospitalisations and deaths and the number of cases of IHM were still higher in men.